A prática social de inclusão de aluno(a)s com deficiência intelectual: um olhar para a práxis e para as vozes de docentes, de discentes e de familiares do(a)s estudantes - Fernandes, Maria José da Silva (2020)
In this doctoral thesis, we investigate the social practice of inclusion of students with intellectual disabilities and the discursive evaluations and representations built in the school context of inclusive education, by teachers, students and their families. We analyzed this practice in two state schools in Minas Gerais, in the regular classrooms of regular education, in the final years of elementary school and in the resource rooms of the Specialised Educational Service, based on observations and semi-structured interviews. The participants in this research are 08 teachers, 10 students and 9 representatives of the parent / guardian segment. To undertake this study, we adopted the theoretical assumptions of Critical Discourse Analysis (ADC), especially Norman Fairclough's dialectical-relational approach (1989, 1999, 2003, 2012), with a focus on representational and identificational meanings. From the representational meaning, we use the interdiscursivity category; of the identificational meaning, the evaluation. For the analysis of the evaluations, we used Martin and White's (2005) Evaluation System. We also adopted the Inclusive Education guidelines as a theoretical framework, mainly the documents that govern it in the state of Minas Gerais, and the official guidelines about teaching reading / literacy contained in the National Curriculum Parameters (PCN), in the Minas Gerais Reference Curriculum (CRMG) and at the National Common Curricular Base (BNCC), thus making a theoretical, methodological, spatial and perception triangulation of the different participants, as directed by Denzim (1970). The data revealed that, despite all the efforts of the teachers, the school inclusion of students with ID, practiced in the schools participating in the research, still needs readjustments and overcoming obstacles and challenges for it to be carried out as proclaimed. in official documents. It is necessary to implement actions that enable the development of the reading competence of the student (s) and the interaction of these student (s) during classes, as some student (s), despite being in the years end of elementary school, have not yet developed the ability to read. Many barriers that still hinder the effective participation of students need to be eliminated, such as the lack of support professional, material resources and training for professionals. The representations and evaluations constructed by teachers and relatives of the students, materialized mainly in the interviews, are mostly related to the beliefs and values of these social actors, who express, predominantly, behavioral evaluations, corresponding to the category Judgment, of the Attitude Subsystem, when referring to the student(s). There are few assessments of Affection, with insecurity and dissatisfaction prevailing. The marks of appreciation identified collaborate with the representations constructed about inclusive education, the school, teaching and students. These evaluation strategies are mostly negative, being materialized through processes, circumstances and attributes, mainly. Finally, we believe that it is necessary to focus especially on the potential of each one of these students, to avoid the naturalization of prejudices and stigmas, very common when focusing on the difficulties of the students, which greatly impairs its development. We hope that this study will contribute to a greater understanding of the process of inclusion of students with ID in public schools in Minas Gerais.